Duchess of Carbon County - Martin, Kat (Unity, Me. : Five Star, 1997)
When a hired gunman came to her small Pennsylvania town, Elaina McAllister knew with one look at his glinting blue eyes that she could never love this insolent stranger. But against all will, she found herself aching for his touch.... He masked his true feelings behind a teasing seduction, but Ren Daniels knew this tender beauty had captured his heart. Destiny would tear them apart when Elaina finds a golden fortune in the Colorado hills -- and becomes the toast of San Francisco's glittering high society. But she yearns for her roguish lover and for the fire of their everlasting passion.
70975